Component composition of essential oil in the North American Pinus L. species introduced to the Southern Coast of Crimea - T. M. Sakhno; Y. V. Plugatar; O. M. Shevchuk; S. A. Feskov; I. V. Bulavin (Труды по прикладной ботанике, генетике и селекции, 2021)
Background. Studying essential oils in conifers is of great scientific and practical interest due to their high bactericidal properties. Their volatiles play an important role in combating pathogenic microflora and removing harmful microorganisms from the air, thus benefiting human health. Conifers are highly effective as part of parklands and urban landscaping.Materials and methods. Pinus radiata D. Don, P. sabiniana Douglas and P. coulteri D. Don grown on the Southern Coast of Crimea were studied. Essential oil was extracted from pine needles by hydrodistillation on Ginsberg devices, and its component composition was analyzed using gas–liquid chromatography on a 6890N system with a 5973N mass selective detector.Results. Among the studied species, P. radiata manifested high essential oil content in needles: 0.15% on the wet weight basis (0.36%, dry weight). Under the conditions of the southern coast of Crimea, the major essential oil components in P. radiata were β-pinene (29.5% of the total essential oil), α-pinene (21.2%) and limonene (12.4%); in P. sabiniana, phenylethyl butyrate (20.5%), limonene (15.2%) and α-pinene (13.7%); in P. coulteri, β-pinene (11.6%), δ-cadinene (11.0%) and α-pinene (10.6%). In the essential oil of P. radiata monoterpenes dominated (74.9%); in P. sabiniana, monoterpenes (38.7%) and their derivatives − alcohols (25.3%) and esters (20.5%); in P. coulteri, sesquiterpenes (38.2%) and monoterpenes (28.8%).Conclusion. The essential oils of P. radiata and P. sabiniana under different climate conditions contained mostly monoterpenes (β-pinene in P. radiata, and α-pinene in P. sabiniana) and their derivatives. The component composition of P. coulteri essential oil was the most variable, with a general tendency towards the predominance of sesquiterpenes and diterpenes; the ratio between those groups and the qualitative composition of sesquiterpenes both varied.